A review on strategies to optimize metabolic stages of anaerobic digestion of municipal solid wastes towards enhanced resources recovery - Edwin N. Richard; Askwar Hilonga; Revocatus L. Machunda; Karoli N. Njau (Sustainable Environment Research, 2019)
Abstract Recently, there are increased efforts by municipals and researchers to investigate the potential of utilizing municipal solid wastes (MSW) for resources recovery. In many parts of developing countries, MSW is mostly collected for disposal with little emphasis on resources recovery. However, the MSW has high organic and moisture contents, and are suitable substrates for anaerobic digestion (AD) process to recover biogas for energy and digestate which can be used as fertilizers or for soil amendments. Resources recovery from the AD process consists of four metabolic stages; hydrolysis, acidogenesis, acetogenesis, and methanogenesis. These metabolic stages can be affected by several factors such as the nature of substrates, accumulation of volatile fatty acids, and ammonia inhibition. In this review, different optimization strategies towards resources recoveries such as pre-treatment, co-digestion, trace elements supplementation, optimization of key parameters and the use of granular activated carbon are discussed. The review reveals that the currently employed optimization strategies fall short in several ways and proposes the need for improvements.